Iron-Catalyzed Carbonyl–Alkyne and Carbonyl–Olefin Metathesis Reactions - Benedikt W. Grau (Catalysts, 2020)
Construction of carbon–carbon bonds is one of the most important tools for the synthesis of complex organic molecules. Among multiple possibilities are the carbonyl–alkyne and carbonyl–olefin metathesis reactions, which are used to form new carbon–carbon bonds between carbonyl derivatives and unsaturated organic compounds. As many different approaches have already been established and offer reliable access to C=C bond formation via carbonyl–alkyne and carbonyl–olefin metathesis, focus is now shifting towards cost efficiency, sustainability and environmentally friendly metal catalysts. Iron, which is earth-abundant and considered as an eco-friendly and inexpensive option in comparison to traditional metal catalysts, fulfils these requirements. Hence, the focus of this review is on recent advances in the iron-catalyzed carbonyl–alkyne, carbonyl–olefin and related C–O/C–O metathesis reactions. The still large research potential for ecologically and economically attractive and sustainable iron-based catalysts is demonstrated.